Coordination matters - Territorial governance in innovation clusters: Comparison of Cité Biotech (Canada) and Polepharma (France) - Wang, Yihan; Bourdin, Sébastien (Management international / International Management / Gestiòn Internacional, 2025)
This paper investigates the territorial governance mechanisms of proximity-based cluster agglomerations and organized proximity-based cluster communities. We argue that the territorial governance mechanisms of clusters consist of the locations of members, the organizational logics, and the roles of institutional intermediaries. Based on the compared case studies of Cité Biotech (Canada) and Polepharma (France), we address the similarities of both types of clusters in terms of local agglomeration, diversity of cluster members, and institutional intermediaries’ roles as brokers and facilitators. We also highlight their differences in external pipelines, logic of belonging, and intermediaries’ roles as mediators, orchestrators, and innovators in the cluster community. Finally, we conclude with the strategic implications for innovation cluster territorial governance.